RESILIENSI SANTRI KORBAN SEXUAL HARASSMENT OLEH PENGASUH PESANTREN: (Analisis Dampak Psikologis Perempuan dalam Bingkai Pesantren dan Stereotype Patriarki) - Rahmawati, Ayu (Program Studi Bimbingan Konseling Pendidikan Islam Fakultas Tarbiyah Institut Agama Islam Ngawi, 2023)
Many pesantren are dubbed as a hotbed of patriarchal culture by the community. Several factors that lead to patriarchal stereotypes in pesantren are, for example, the phenomenon of interpretation of the meaning of the yellow Islamic classic book, where in the yellow Islamic classic book there are no authors who are female, even in books such as the uqudulijain book, the differences in rights and obligations between men and women are evident, which are considered more favorable to men than women. In this case, the author tries to analyze the position of women in pesantren, and also tries to review how the position of women who are discriminated against in pesantren, and how the resilience of santri who experience discrimination in real form by their own caregivers. The research methodology in this study is to use a qualitative approach by extracting data using observation and interviews. With the focus of our research is on students who experience sexual violence by their own caregivers in one of the boarding schools in East Java. From the results of our research, that there are students who have high resilience so that after the incident they managed to get up and still instill positive values that can be taken from their learning while in the pesantren. However, there are also some of our informants who direct their disappointment to negative things such as smoking, drinking alcohol, and etc. Keywords : Sexual Harassment, Resilience, Patriarchy